Intervensi Bimbingan Klasikal Dengan Teknik Modeling Untuk Meningkatkan Kematangan Karier Remaja - Rasyidah Salsabila, Sofia; Purwo Hartanto, Agit (Jurnal Bimbingan dan Konseling Pandohop, 2025)
Career maturity reflects an individual’s readiness to make career decisions independently, rationally, and responsibly. A low level of career maturity among adolescents can hinder future planning and increase the risk of youth unemployment. This study aimed to examine the effectiveness of classical guidance interventions using modeling techniques (covert and symbolic) in enhancing adolescent career maturity. Utilizing a quantitative approach with a one-group pretest-posttest pre-experimental design, the study involved 23 adolescents from the Mawar 3 Taman Baru Teenage Integrated Health Post. The instrument used was a career maturity questionnaire that had been validated and shown to be reliable (α = 0.898). The intervention was conducted in two sessions using video media and reflective activities. Paired Sample t-Test analysis revealed a significance value of 0.000 (p < 0.05), with the average score increasing from 72.43 to 81.39 after the intervention. These findings indicate that modeling techniques are effective in improving adolescents’ career understanding, planning, exploration, and orientation. Practically, the results highlight the importance of integrating modeling techniques into classical guidance services in schools and communities as a preventive and developmental intervention strategy. This study also contributes to the literature on the effectiveness of modeling techniques in community-based adolescent counseling contexts.